Transport equity impacts of green growth initiatives in Vietnam: An empirical evaluation using panel data - An Minh Ngoc; Yasuhiro Shiomi; Huynh Quang Nghi; Muhammad Faizan ul Haq; Alessandro Severino; Doanh Nguyen-Ngoc (Transportation Research Interdisciplinary Perspectives)
This study investigates the impact of first-generation Green Growth (GG) initiatives on transport equity in Vietnam. Since 2012, the GG initiatives have focused on reducing Greenhouse Gas (GHG) emissions and enhancing energy efficiency by promoting a shift from private to public transport. The transport equity impacts of these initiatives are studied and quantified using comprehensive data from the Vietnam Household Living Standards Survey (VHLSS) between 2014 and 2020. To explore horizontal and vertical equity, we developed a transit service index to measure changes in the implementation of GG initiatives and employed the Entropy weighting analysis (EWA) method, cluster analyses alongside the Lorenz curves, and the Gini index. The spatial distribution of transport equity changes is mapped to illustrate regional variations in response to GG initiatives. Results are presented through Lorenz curves, showcasing improvements in horizontal transport equity across Vietnam’s regions, while vertical equity among provinces is assessed using the Gini index. The study contributes in practice by providing evidence to policymakers for a better understanding of the GG initiatives’ impacts. Finally, the study proposes several implications for policymakers to create efficient GG measures to retain transport equity.